ECMO in the adult patient - Vuylsteke, Alain; Brodie, Daniel; Combes, Alain; Fowles, Jo-Anne; Peek, G. J (Cambridge University Press, 2017)
"Extracorporeal membrane oxygenation (ECMO) is developing rapidly, and is now part of the toolkit for the management of all patients with severe respiratory or cardiac failure. Clinicians of all disciplines are in need of a simple manual, easy and fun to read, that will take them through the management of these patients, explaining the principles of safe and successful practice. Part of the Core Critical Care series, this book is an easy-to-read guide for the aspiring ECMO clinician. Doctors, nurses, physiotherapists, dieticians, pharmacists and all other key members of the team will learn the basics required to better understand the technology and care of the patient. The experienced clinician will enjoy reading through the chapters, which present structured thoughts and knowledge acquired through clinical experience"--Provided by publisher.
Core critical care
Keywords: Extracorporeal Membrane Oxygenation; urgentní lékařství; mimotělní membránová oxygenace